2008
DOI: 10.1007/s11033-008-9365-6
|View full text |Cite
|
Sign up to set email alerts
|

Cloning, expression and subcellular distribution of a Rana grylio virus late gene encoding ERV1 homologue

Abstract: An essential for respiration and viability (ERV1) homologue, 88R, was cloned and characterized from Rana grylio virus (RGV). Database searches found its homologues in all sequenced iridoviruses, and sequence alignment revealed a highly conserved motif shared by all ERV1 family proteins: Cys-X-X-Cys. RT-PCR and western blot analysis revealed that 88R begins to transcribe and translate at 6 h postinfection (p.i.) and remains detectable at 48 h p.i. during RGV infection course. Furthermore, using drug inhibition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 37 publications
0
14
0
Order By: Relevance
“…Transfected cells were incubated 24 h at 25°C and then fixed and stained with Hoechst 33342 as described previously [51]. All samples were examined under a Leica DM IRB fluorescence microscope.…”
Section: Methodsmentioning
confidence: 99%
“…Transfected cells were incubated 24 h at 25°C and then fixed and stained with Hoechst 33342 as described previously [51]. All samples were examined under a Leica DM IRB fluorescence microscope.…”
Section: Methodsmentioning
confidence: 99%
“…RGV has been recognized as a member of the family Iridoviridae and is closely related to FV3, based on previous studies on morphogenesis, cellular interaction, antigenicity, restriction fragment length polymorphism (RFLP) and major capsid protein (MCP) sequence similarity [15][16][17][18]. To date, some genes of RGV have been identified and characterized, such as 3b-hydroxysteroid dehydrogenase (3b-HSD), deoxyuridine triphosphatase (dUTPase), an envelope protein gene (53R), thymidine kinase (TK) and a gene belonging to the ''essential for respiration and viability'' family (ERV1) [19][20][21][22][23][24]. We found that RGV could induce apoptosis mediated by mitochondria [25].…”
mentioning
confidence: 99%
“…A 9GL deletion mutant displayed a 2-log drop in viral yield, and, of the virions that formed, 90-99 % contained acentric nucleoid structures. Like ASFV, the RGV ERV1 homolog (88R) is a late protein (Ke et al 2009 ). It contains the highly conserved ERV1 motif Cys-X-X-Cys and was detected in both the nucleus and cytoplasm.…”
Section: Erv1mentioning
confidence: 99%